GLAM-Based Management of Islamic Manuscripts From Local Wisdom of Jember to Global Harmony in Islamic Scholarship - Hidayat, Rofiq (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study explores the GLAM-based management (Gallery, Library, Archives, and Museum) of Islamic manuscripts in the UIN KHAS Jember Library as a sustainable effort to preserve local Islamic wisdom while contributing to global scholarly harmony. The research employs a qualitative descriptive approach with case studies and document analysis of manuscript preservation practices. Findings indicate that GLAM provides a comprehensive framework for integrating conservation, digitization, and dissemination of manuscripts, transforming local heritage into global academic assets. Moreover, the approach enhances intercultural understanding, nurtures tolerance, and strengthens the relevance of Islamic scholarship in a pluralistic society. The study highlights the role of GLAM not only as a preservation tool but also as a strategic model of educational management to bridge local wisdom and global harmony